Unplugged gamification in education: Developing computational thinking skills through embodied gameplay - Christopoulos, Athanasios; Mystakidis, Stylianos; Stylios, Chrysostomos; Tsoulos, Ioannis G. (Informa UK Limited, 2025)
The study examines the effectiveness of unplugged gaming activities for stimulating Computational Thinking (CT). Departing from traditional, sedentary digital gamification, physically active alternatives were sought to reduce the potential health risks of excessive screen time. Additionally, efforts were made to engage girls. Using a mixed-methods approach, 311 adolescents (13-15 years old) were randomly assigned to an escape room or treasure hunt, where over a five-day summer vacation program, they participated in activities designed to improve CT components. Quantitative analysis revealed significant improvements in CT test scores after the intervention in both conditions for both genders. Qualitative analysis confirmed these findings and further highlighted their impact on engagement. Collaborative learning and cognitive challenge were positive aspects, while some challenges related to team dynamics and task complexity were also identified. The study demonstrates the potential of physically active gamification in CT education and highlights the importance of taking gender-specific experiences into account.